Analisis dan Perancangan Sistem Pengelolaan Inventory di PT Bright Mobile Telecommunication - Tantha, Subhasita Manggala; Kuswanto, Veri (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2025)
Use of office supplies in the General Affairs section PT BMT is quite high due to the number of employees Lots. However, inventory management is still facing several problems, such as not yet Actual stock data that can be accessed at any time, frequently the occurrence of stock of certain goods running out, as well as difficulties in Manage incoming and outgoing goods data. To overcome these problems, then a system was created inventory that allows stock monitoring, easier transaction recording, as well as data analysis which is more efficient, so that stock is always well controlled good and avoid running out of goods. This system designed using the prototyping method, starting from user needs analysis, planning, design display, coding, and testing to ensure suitability. This system also provides stock reports, transaction data, and stock cards that help analyze goods needs and monitoring pending purchases in stock. By implementing this system at PT Bright Mobile Telecommunication, management, control, and inventory monitoring becomes more effective, stock information always accurate, and stock maintained optimally.